A comparative automated content analysis approach on the review of the sharing economy discourse in tourism and hospitality. Issue 1 (2nd January 2019) - Cheng, Mingming; Edwards, Deborah
Abstract : Using the sharing economy (SE) as the context, this article provides a coherent and nuanced methodological understanding of automated content analysis (ACA) in tourism and hospitality (TH) field. By adopting a comparative ACA approach, the paper compares the current TH Western academic literature of the SE with news media discourse in TH from the period 2011–2016 (August) (inclusive). The emerging issues from the news media discourse, such as mobility, SE companies and the role of government, are absent in current tourism academic research. Findings reveal that ACA can facilitate a more systematic comparison between different sources of data. This paper offers a starting point for tourism scholars to methodologically engage with ACA that can draw useful insights on a particular context.